La Brucellose aigue au niveau de l’EPH mixte Laghouat 2022 - DR. BOUNASLA ASMA; DR. ATTIA HADJER (My University, 2023)
Brucellosis or Malta fever, is a ubiquitous anthropozoonosis, due to bacteria of the genus Brucella, which 04 species are pathogenic for humans (B.melitensis, B.abortus, B.buis, B.canis), the most frequent and virulent in Algeria is B.melitensis followed by B.abortus. Clinically unspecific evolving in 3 phases: acute, subacute, chronic, its prognosis can be bad due to complications type of secondary focalizations, in Algeria its treatment is well codified (the 2018 instruction). Our epidemiological investigation carried out on acute brucellosis at the mixed EPH of Laghouat over a period of 12 months, from January 1, 2022 until December 31, 2022, 34 cases notified from different municipalities of the town, municipality of Laghouat, El Khnegue, El Assafia, El Houaita. which 29 patients came mainly from the town of Laghouat. From our study we noticed that 21 cases were declared during the Summer period. Brucellosis affects both men and women, in our study a male predominance with sex ratio = 1.61 M/F was marked. On the clinical level, we noticed that the prolonged fever was identified in 33 patients, followed by the sudoro-algic syndrome in 32 cases, moreover 04 cases had presented spondylodicite, including 2 cases complicated by epiduritis, and 01 only case presented with laterocervical lymphadenopathy. Therapeutically, 25 cases put on the GENTAMYCINE + DOXYCYCLINE association, 04 patients put on the DOXYCYCLINE + RIFAMPICIN association, 02 cases (one child and a pregnant woman) put on the COTRIMOXAZOLE + GENTAMYCINE association. During our study, the regression of sudoro-algic syndrome and fever were noted in all our patients after 5 days, on the other hand the 34 cases reported the persistence of asthenia for a few weeks.
68 p.